2017
DOI: 10.5603/gp.a2017.0100
|View full text |Cite
|
Sign up to set email alerts
|

Mig-7 expression and vasculogenic mimicry in malignant ovarian tumors

Abstract: Objectives:To investigate the possible association of vasculogenic mimicry (VM), VE-cadherin and MIG-7 expression with clinicopathological features of women with malignant ovarian masses. Material and methods:VM was studied with the PAS reaction and VE-cadherin was assessed with immunohistochemistry in 108 women with malignant ovarian tumors. Additionally, quantitative expression of MIG-7 mRNA was performed in 52 ovarian cancers with qRT-PCR.Results: VM was found in 48/108 cases (44%), more often in higher FIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Interestingly, high expression of VE-cadherin and EphA2 has been found in clinical samples from ovarian cancer patients that exhibit a highly invasive phenotype (84, 85). Additionally, other studies demonstrated that MMP-2 and MMP-14 are also overexpressed in ovarian cancer samples, which is associated with poor clinical outcome (38, 86).…”
Section: Mechanisms and Signaling Molecules Involved In Vm In Ovarianmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, high expression of VE-cadherin and EphA2 has been found in clinical samples from ovarian cancer patients that exhibit a highly invasive phenotype (84, 85). Additionally, other studies demonstrated that MMP-2 and MMP-14 are also overexpressed in ovarian cancer samples, which is associated with poor clinical outcome (38, 86).…”
Section: Mechanisms and Signaling Molecules Involved In Vm In Ovarianmentioning
confidence: 99%
“…Furthermore, Ln5γ2 activates the endothelial growth factor receptor (EGFR) which promotes the expression of the migration-inducing protein 7 (Mig-7), stimulating invasion and VM (94). A study carried out in ovarian cancer samples revealed an association of VM with VE-cadherin and Mig-7 expression (84). It was observed that ovarian tumors without VM frequently expressed low levels of VE-cadherin compared to those with VM.…”
Section: Mechanisms and Signaling Molecules Involved In Vm In Ovarianmentioning
confidence: 99%
See 1 more Smart Citation
“…VE-cadherin expression was highly upregulated in VM-positive patients and in SKOV3 and OVCAR3 ovarian cancer cells under hypoxic conditions (45). It has also been shown that VE-cadherin expression levels are closely associated with the propensity for VM in ovarian cancer cells and malignant ovarian cancer tissues (46,47), suggesting biological significance of VE-cadherin in VM in malignant ovarian cancers.…”
Section: Vascular/angiogenesis Signaling In Vmmentioning
confidence: 95%
“…Mig-7 significantly affects tumor migration and invasion in hepatocellular carcinoma and osteosarcoma, while it is essential for proliferation and invasion in ovarian cancer [8,9]. Further, Mig-7 is overexpressed in highly invasive tumors but not in non-invasive malignant cells [10][11][12][13], suggesting an important role in tumor invasion. Additionally, knocking down Mig-7 attenuates the invasiveness of U87MG cells [12].…”
mentioning
confidence: 98%